Competency-based education in midwifery: A comprehensive review of implementation strategies and outcomes in developing regions - Prima Kusrini; Ari Indra Susanti (Inovasi Kurikulum, 2025)
Competency-based education (CBE) is increasingly adopted as a reformative approach in midwifery education, particularly within developing regions such as Africa and South-East Asia. It aims to improve the preparedness of midwives to address complex maternal and newborn health challenges. This literature review employed a comprehensive analysis of 14 peer-reviewed studies, utilizing qualitative and mixed-method research designs. The studies included systematic reviews, gap analyses, and interview-based investigations across diverse educational settings. The review identified that CBE significantly enhances clinical competencies, theoretical knowledge, and professional self-confidence among midwifery students. Practical implementation strategies included the integration of simulation-based learning, continuous assessment, and mentorship models. However, significant barriers included inadequate institutional resources, faculty training, and resistance to pedagogical change. CBE offers a structured and outcomes-driven educational model that aligns theoretical instruction with practical skills acquisition. Its adoption addresses persistent gaps in midwifery training and contributes to workforce readiness in resource-limited settings. The findings suggest that CBE can serve as a transformative framework for midwifery education in developing regions. Policy support, investment in educator training, and curriculum reform are essential to realize its potential and improve reproductive health outcomes fully.   Abstrak Model pendidikan berbasis kompetensi (CBE) kini semakin diadopsi dalam program pendidikan kebidanan di negara-negara berkembang sebagai upaya untuk meningkatkan kesiapan mahasiswa dalam praktik klinis serta menjawab kekurangan tenaga profesional di bidang kesehatan ibu dan bayi. Kajian literatur ini melibatkan analisis terhadap 14 artikel ilmiah yang telah melalui proses peer-review. Pendekatan yang digunakan meliputi metode kualitatif dan campuran, mencakup tinjauan sistematis, analisis kesenjangan, serta studi wawancara yang dilakukan di berbagai institusi pendidikan di kawasan Afrika dan Asia Tenggara. Studi-studi yang dikaji menunjukkan bahwa penerapan CBE secara signifikan memperkuat keterampilan praktik, pemahaman konseptual, dan rasa percaya diri mahasiswa kebidanan. Pendekatan yang paling efektif mencakup penggunaan simulasi dalam pembelajaran, pendampingan akademik, dan penerapan alat evaluasi berbasis kompetensi. Kendati demikian, implementasi CBE masih menghadapi hambatan, seperti keterbatasan sumber daya institusional, kurangnya pelatihan bagi tenaga pengajar, dan resistensi terhadap perubahan kurikulum. CBE berperan penting dalam menjembatani teori dan praktik, serta menawarkan pendekatan sistematis untuk meningkatkan mutu pendidikan kebidanan. Fokusnya pada pencapaian hasil memungkinkan pembentukan tenaga profesional yang lebih siap menghadapi tantangan di lapangan. Penerapan CBE memiliki potensi besar dalam meningkatkan kualitas pendidikan kebidanan di wilayah dengan sumber daya terbatas. Untuk mencapai dampak yang berkelanjutan, diperlukan dukungan berupa pelatihan tenaga pengajar, pembaruan kebijakan pendidikan, serta penguatan infrastruktur institusi. Keberhasilan implementasi model ini berkontribusi pada peningkatan layanan kesehatan ibu dan bayi serta penguatan kapasitas tenaga kesehatan di negara-negara berkembang.. Kata Kunci: kebidanan; pendidikan berbasis kompetensi ; pendidikan tenaga kesehatan; strategi implementasi